The Role of Religious Leaders in Promoting Healthy Habits in Religious Institutions - Anshel, Mark H. (Journal of religion and health, 2014)
The growing obesity epidemic in the West, in general, and the USA, in particular, is resulting in deteriorating health, premature and avoidable onset of disease, and excessive health care costs. The religious community is not immune to these societal conditions. Changing health behavior in the community requires both input from individuals who possess knowledge and credibility and a receptive audience. One group of individuals who may be uniquely positioned to promote community change but have been virtually ignored in the applied health and consulting psychology literature is religious leaders. These individuals possess extraordinary credibility and influence in promoting healthy behaviors by virtue of their association with time-honored religious traditions and the status which this affords themas well as their communication skills, powers of persuasion, a weekly (captive) audience, mastery over religious texts that espouse the virtues of healthy living, and the ability to anchor health-related actions and rituals in a person's values and spirituality. This article focuses on ways in which religious leaders might promote healthy habits among their congregants. By addressing matters of health, nutrition, and fitness from the pulpit and in congregational programs, as well as by visibly adopting the tenets of a healthier lifestyle, clergy can deliver an important message regarding the need for healthy living. Through such actions, religious leaders can be effective agents in promoting critical change in these areas.